2001
DOI: 10.1046/j.1471-4159.2001.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylaspartate, a marker of both cellular dysfunction and neuronal loss: its relevance to studies of acute brain injury

Abstract: To evaluate the contribution of cellular dysfunction and neuronal loss to brain N-acetylaspartate (NAA) depletion, NAA was measured in brain tissue by HPLC and UV detection in rats subjected to cerebral injury, associated or not with cell death. When lesion was induced by intracarotid injection of microspheres, the fall in NAA was related to the degree of embolization and to the severity of brain oedema. When striatal lesion was induced by local injection of malonate, the larger the lesion volume, the higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(140 citation statements)
references
References 39 publications
7
131
2
Order By: Relevance
“…In rats treated with 3NP, NAA decrease was observed selectively in the striatum before any cell loss, but was associated with motor symptoms (Demougeot et al, 2001). Also, a similar selective and early striatal decrease in NAA was observed in 3-NP treated primates (Dautry et al, 2000).…”
Section: Impairments In Energy Metabolism Decrease Naa Levels In Brainmentioning
confidence: 70%
“…In rats treated with 3NP, NAA decrease was observed selectively in the striatum before any cell loss, but was associated with motor symptoms (Demougeot et al, 2001). Also, a similar selective and early striatal decrease in NAA was observed in 3-NP treated primates (Dautry et al, 2000).…”
Section: Impairments In Energy Metabolism Decrease Naa Levels In Brainmentioning
confidence: 70%
“…Studies using MRSI in children also showed NAA/Cre reductions early after injury (10) as well as decreased NAA/Cho ratios up to three years post injury (36). Animal models of TBI that demonstrated decreases of NAA, found associations with regions of diffuse axonal injury (37) and neuronal loss (38,39). Therefore, the association of reduced NAA with poor cognitive outcome provides further evidence that NAA functions as a marker for neuronal and axonal injury in the setting of TBI in humans.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, patients were imaged on average 6 Ϯ 4 days following injury, with some as long as 16 days after injury. Animal models have shown that metabolites such as Cho and mI increase soon after injury (38) whereas, NAA associated with neuronal dysfunction may remain depressed for days to weeks depending on the severity of injury (41) and may be permanent if neuronal loss has occurred (39). The time course for metabolic changes following TBI is not well established in humans and may vary by age as well as injury severity.…”
Section: Discussionmentioning
confidence: 99%
“…8,13 For example, although traumatic brain injury (TBI) is associated with immediate reductions in NAA, several studies have reported that these levels appear to recover significantly with time, which could not occur if NAA levels were decreased by cell death alone. 13,14 In fact, research on cerebral injury by Demougeot et al 15 has indicated that cellular dysfunction can actually cause greater measurable reductions in NAA than neuronal loss. Abnormally low ratios of NAA/Cr þ PCr have been observed in patients with a number of mitochondrial encephalomyopathies, 16 and studies using mitochondrial respiratory chain inhibitors have also shown that reductions in NAA are correlated with decreases in O 2 consumption and ATP production.…”
mentioning
confidence: 99%